Collagen peptides from Acaudina molpadioides prevent CCl4‐induced liver injury via Keap1/Nrf2‐ARE, PI3K/AKT, and MAPKs pathways. Issue 5 (2nd April 2022) - Li, Jie; Li, Yan; Lin, Saijun; Zhao, Wei; Chen, Yan; Jin, Huoxi
Abstract: Collagen peptide from Acaudina molpadioides (AMP) showed antioxidative activity in H2 O2 ‐induced RAW264.7 cells in our pervious study. In this study, it was observed that AMP could effectively improve the morphology and function of liver in CCl4 ‐induced mice. After 200 mg/kg AMP treatment, the content of MDA in liver decreased by 62.3%, and the level of antioxidant enzymes (SOD, GSH‐Px, and CAT) increased by more than 65%. Western blot results disclosed that AMP (200 mg/kg) upregulated the Nrf2 level by 73.8% and downregulated Keap1 by 41.0% in CCl4 ‐induced mice liver. The levels of p‐ERK, p‐JNK, and p‐p38 in 200 mg/kg AMP treatment groups decreased by 57.3%, 40.9%, and 40.6%, but the levels of p‐PI3K and p‐AKT increased by 162.6% and 60.3%, respectively. Furthermore, the trends of Nrf2, Keap1, p‐ERK, p‐JNK, p‐p38, p‐PI3K, and p‐AKT levels in H2 O2 ‐induced RAW264.7 cells after AMP treatment were similar to the results in CCl4 ‐induced mice liver. These findings provided evidence that AMP exerted antioxidant activity via Keap1/Nrf2‐ARE, PI3K/AKT, and MAPKs pathways in vivo and in vitro. Therefore, the collagen peptide from A. molpadioides might represent a novel functional food to prevent acute liver injury via attenuation of oxidative stress.